Distribution of Benthic Foraminifera in Intertidal Sabkha of Al-Kharrar Lagoon, Saudi Arabia: Tools to Study Past Sea-Level Changes - Al-Dubai, Talha A.; Bantan, Rashad A.; Abu-Zied, Ramadan H.; Al-Zubieri, Aaid G.; Jones, Brian G. (Frontiers in Marine Science, 2022)
Contemporary foraminiferal sediment samples were collected from the intertidal sabkha of Al-Kharrar Lagoon, Saudi Arabia, to study the vertical distribution of foraminifers and, based on a modern training set, their potential to develop a predictor of former sea-level changes in the area. Based on hierarchical cluster analysis, the intertidal sabkha is divided into three vertical zones (A, B, and C) represented by three foraminiferal assemblages, where agglutinated species occupied Zone A and calcareous species occupied the other two zones. In Zone A (high intertidal), Agglutinella compressa, Clavulina angularis and C. multicamerata are dominant species with a minor presence of Peneroplis planatus, Coscinospira hemprichii, Sorites orbiculus, Quinqueloculina lamarckiana, Q. seminula, Ammonia convexa and A. tepida. In contrast, in Zone B (middle intertidal) the most abundant species are P. planatus, C. hemprichii, S. orbiculus, Q. lamarckiana, Q. seminula and Q. laevigata, while Zone C (low intertidal) is characterized by C. hemprichii, Q. costata, S. orbiculus, P. planatus, A. convexa, A. tepida, Spiroloculina communis, and S. costigera. A transfer function for sea-level reconstruction was developed using a modern dataset of 75 contemporary sediment samples and 99 species collected from several transects across the sabkha. The model provided an error of 0.12 m, suggesting that intertidal foraminifers can be used to assess past sea-level changes with high precision in Al-Kharrar Lagoon, and adjacent regions.